New Method To Generate Enzymatically Deficient Clostridium difficile Toxin B as an Antigen for Immunization - Genth, Harald (American Society for Microbiology, 2000)
The family of the large clostridial cytotoxins, encompassing Clostridium difficile toxins A and B as well as the lethal and hemorrhagic toxins from Clostridium sordellii, monoglucosylate the Rho GTPases by transferring a glucose moiety from the cosubstrate UDP-glucose. Here we present a new detoxification procedure to block the enzyme activity by treatment with the reactive UDP-2′,3′-dialdehyde to result in alkylation of toxin A and B. Alkylation is likely to occur in the catalytic domain, because the native cosubstrate UDP-glucose completely protected the toxins from inactivation and the alkylated toxin competes with the native toxin at the cell receptor. Alkylated toxins are good antigens resulting in antibodies recognizing only the C-terminally located receptor binding domain, whereas formaldehyde treatment resulted in antibodies recognizing both the receptor binding domain and the catalytic domain, indicating that the catalytic domain is concealed under native conditions. Antibodies against the native catalytic domain (amino acids 1 through 546) and those holotoxin antibodies recognizing the catalytic domain inhibited enzyme activity. However, only antibodies against the receptor binding domain protected intact cells from the cytotoxic activity of toxin B, whereas antibodies against the catalytic domain were protective only when inside the cell.